Evaluation of targeted next-generation sequencing for microbiological diagnosis of acute lower respiratory infection - Yang, Fengzhen; Jiang, Lihua; Cao, Qingmei; Yi, Maoli; Zhao, Qi (Frontiers in Microbiology, 2025)
PurposeTo evaluate the performance of targeted next-generation sequencing (tNGS) in pathogen detection in acute lower respiratory infection.MethodsThe retrospective study was conducted between July 2023 and May 2024 at the Yantai Yuhuangding Hospital. Patients with acute lower respiratory infections were included. Qualified sputum or bronchoalveolar lavage fluid samples were collected for tNGS and conventional microbiological tests(CMTs), including culture, staining, polymerase chain reaction (PCR), and reverse transcription-PCR (RT-PCR). The time required and cost were counted.ResultsA total of 968 patients were enrolled. Study analysis discovered 1,019 strains of bacteria, 259 strains of fungi, 302 strains of viruses, 76 strains of Mycoplasma pneumoniae, and two strains of Chlamydia psittaci using tNGS. In addition, tNGS also identified 39 mecA, four KPC, 19 NDM, and two OXA-48 genes. The positive rates for bacteria, fungi, viruses, mycoplasma, and chlamydia obtained using tNGS were significantly higher than those determined using traditional methods. Among them, tNGS showed high consistence with mycobacterium DNA test, influenza A (H1N1) virus nucleic acid test and COVID-19 nucleic acid test. Poor consistency between drug resistance genes and bacterial resistance phenotypes was found. In addition, tNGS also had advantages over traditional methods in terms of detection time and cost.ConclusionCompared to traditional methods, tNGS had higher sensitivity in detecting bacteria, fungi, viruses, and other pathogens in acute lower respiratory infection, and also had the advantages of timeliness and cost-effectiveness, making it a promising method for guiding clinical diagnosis.